Republic of Latvia : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper examines the prospects for Latvia continuing to rapidly reduce its distance from the productivity frontier. It looks at the empirical record of countries that have in the past attained a similar relative level of income to that of Latvia at present, to gauge the plausibility of the forecast for Latvia's medium term GDP growth of about 4 percent per year. It highlights that more than one-third of the countries reaching a similar stage of development managed to sustain higher subsequent growth. The paper also confirms the importance of investment and structural reforms for Latvia's future convergence, using a sector-level analysis.